Effects of Fe addition on pyrolysis characteristics of lignin, cellulose and hemicellulose. (April 2023) - Ge, Lichao; Zhao, Can; Zuo, Mingjin; Du, Yuying; Tang, Jie; Chu, Huaqiang; Wang, Yang; Xu, Chang
Abstract: In this paper, the pyrolyzed influence of Fe contents (0%, 1% and 5%) on the lignin, cellulose and hemicellulose were carried out by thermogravimetric and Fourier transform infrared spectroscopy. The pyrolysis process, kinetic characteristics and release characteristics of the pyrolysis products on the three major components were studied. The results showed that the addition of Fe increases the yield of cellulose biochar. The yield of lignin and hemicellulose biochar are also related to the addition of Fe. The kinetic analysis showed that Fe supplementation significantly decreases the activation energy of lignin, but increases the activation energy of cellulose, while the activation energy of hemicellulose was closely related to Fe addition (149.95 kJ/mol under 1% Fe and 127.84 kJ/mol under 5% Fe). The release characteristics of the pyrolysis products showed that the observed pyrolysis products mainly included H2 O, CH4, CO2 and CO. An addition of 5% Fe increased CH4, CO and CO2 production in the pyrolysis process of the three components and produced less H2 O. Highlights: The addition of Fe significantly increases the yield of cellulose semi-coke. The semi-coke yield of lignin and hemicellulose is related to the amount of Fe. The Ea of lignin decreased when 1% (3.32%) and 5% (4.02%) Fe were added. The Ea of cellulose increased when 1% (0.10%) and 5% (1.84%) Fe were added. 5% Fe significantly increases CH4 and CO production for lignin, cellulose and hemicellulose.